Surgical treatment of giant seminal vesicle cyst with ureteral compression: a case report - Gu, Zhuoran; Sun, Liang; Zhang, Wentao; Geng, Jiang; Jiang, Lei; Chen, Yifan (Frontiers in Surgery, 2025)
BackgroundSeminal vesicle cysts (SVCs) are rare benign diseases in men and are commonly asymptomatic. Giant SVCs with complications there are no standard treatments for SVCs, however surgical intervention is required for giant SVCs accompanied with complications.Case summaryWe present one case of a 49-year-old male patient diagnosed with giant SVC. Chief complaint of this patient was persistent gross hematuria for 1 week. Both a computed tomography (CT) and magnetic resonance imaging (MRI) scans indicated the presence of a cystic mass in left seminal vesicle with hemorrhage, of which the maximum diameter is 6.5 cm. Additionally, Giant SVC squeezed the prostate and lower ureter, leading to the dilatation of the left upper ureter and hydronephrosis. After a thorough preoperative evaluation, a laparoscopic resection of SVC and left ureteral stenting were performed. The subsequent pathological analysis identified a seminal vesicle cyst inflammatory infiltration. Postoperative follow-up indicated no abnormalities in left seminal vesicle.ConclusionLaparoscopic surgery is recommended for giant SVCs with complications.